Representing by Outlines. The Mountain, Described through its Contour (TEST XY. Critical review of studies on the representation of architecture and use of the image in science and art, 2025)
The mountain’s profile is recognized as one of the distinctive elements by which it is identified, its reading by contrast with the background sky characterising its iconic recognition. In this sense, the paper investigates the representation of the mountain through the graphic form of the profile, understood as the drawing that reproduces the extreme line of its outline. Consider the triangular profile drawn freehand as the ultimate synthesis of the concept of the mountain but also the detailed one crafted by mountaineers to illustrate the new routes they have travelled; the topographical profile as the scaled representation on a Cartesian plane of the elevation trend along a planimetric line; the artistic profile (as realistic as it is abstract) that the illustrator draws to describe the mountain through captivating graphic artefacts; the profile of the mountain routes in bicycle hiking or great and epic stage races; the profile found in the logos of corporate and territorial brands, where both real and imagined mountains are featured. The contribution adopts a taxonomic approach to the varied alternation of modes and typologies representing the mountain profile, which symbolically take on the figurative meaning of different ways and types of looking at mountains, with the aim of fostering visual keys to interpreting its role as an identity and shared heritage.
Keywords: form; identity; perception